Issues Facing Primary School Teachers in Assam with a Focus on the Nalbari District in Assam (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The process of education elevates individuality to a completely new level. To be in tune with the ever-changing world requires constant effort. Education therefore has a tight relationship with human life. Beginning at birth, it remains constant all the way through life and death. It includes everything that was learned and experienced during early life, childhood, adolescence, and youth. When it comes to determining a person's future and helping to shape their character, education is the most powerful tool available.A continuously substantial component of the entire educational framework is made up of primary education. The first official stage of education is primary education, which comes after preschool or kindergarten. Primary education, usually referred to as primary education, starts at age five or six and finishes at age eleven or thirteen. The foundation for a child's physical, mental, emotional, intellectual, and social growth is the education they receive in formal institutions. For an impoverished state like Assam to thrive at all, primary education is essential.The state of Assam has a well-known, restrictive educational system that dates back to ancient times. During Assam's medieval era, there existed an indigenous educational system. The government has periodically implemented a number of programs to advance primary education in the state since independence. With specific reference to the Nalbari District, an attempt has been made to investigate the issues surrounding primary education in Assam in this study. The report also asks on the number of kids enrolled in and out of the Nalbari District's primary schools. Additionally, the study made several recommendations for necessary actions to address the current issues facing the primary schools in the chosen area.